Aplicação de modelos matemáticos em Curvas de ruptura de poluentes Biogás (2016)
In this project biogas was purifed using separate packed bed adsorption columns using activated carbon, iron flings, kaolin and calcium carbonate. Experiments were performed in 2cm diameter and 9cm length polypropylene columns. The breakthrough curves were constructed with an average biogas fow of 2.2L per day. Samples were taken for almost 28 days, which biogas composition were quantifed using gas chromatography and online gas analyser. The curves were ftted to three mathematical models. Using activated carbon a correlation coeffcient of 0.9987 and 0.9991 for hydrogen sulfde (H2S) and ammonia (NH3), respectively, were obtained. In the case of iron flings a correlation coeffcient of 0.9945 and 0.9975 for H2S and NH3, respectively, were obtained. Using kaolin a correlation coeffcient of 0.9994 and 0.9885 for H2S and NH3, respectively, were obtained. Finally, using calcium carbonate with a correlation coeffcient of 0.9988 and 0.9985 for H2S and NH3, respectively, were obtained. Removal percentage of H2S and NH3 using activated carbon was 72.6 %, iron flings was 74.1 %, kaolin was 32.7% and calcium carbonate was 65.4 %.